(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current status of social work implementation at Pho Noi General Hospital, Hung Yen province in the first quarter of 2024. Method: Cross-sectional descriptive study. Results: Most of the patients’s needs were met, the highest being in the services of guiding and supporting examination and treatment procedures (84.7%) and providing treatment plans, disease progression, and prognosis (84.8%). The services with a low level of response were mainly concentrated in the group of psychological and social support services (including counseling, consultation, psychotherapy), as well as the group of services connecting resources and supporting medical expenses (including cash support and gifts of personal items for patients, accommodation support for relatives). This result is also consistent with studies at other hospitals and is also in line with the actual situation of Pho Noi General Hospital, when the Social Work Team has a short working time with limited resources. Conclusion: This study suggests the need to supplement resources, especially qualified personnel in the field of psychology and social work, to contribute to improving the effectiveness of social work services at Pho Noi General Hospital.